ASPECTE ALE EDUCAŢIEI ECONOMICE LA ORELE DE GEOGRAFIE - USM ADMIN (Moldova State University, 2012)
This investigation The development of the economical skills has attacked one of the important topical problems, which is economic education. There are examined conceptions and theories which promote elaboration of the step revaluation in practice of the economic education. It has been established that the economic education is the component part of the Problems of the Contemporary World and it is centered on objectives and educational contents. It represents the formation of the pupil personality through assimilating the work experience, through attitude towards all what surrounded him, towards the community in which he live and pay attention on economic training for personal life and initiate in problems of the economy, it will form a first step in direction of the economic competences which can be cognitive - theoretic and active - practice.